2022
DOI: 10.31817/vjas.2022.5.1.06
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Analysis and Antioxidant and Alpha-glucosidase Inhibitory Activities of the Stem Bark of Dialium cochinchinense Pierre

Abstract: The purpose of this study was to determine the phytochemical compositions and to evaluate the biological activity of the stem bark of Dialium cochinchinense. The phytochemical analysis showed the presence of steroids, terpenoids, anthraquinones, saponins, and phenolics in the stem bark of D. cochinchinense. The optimal extraction conditions were 70% ethanol at 30°C for 40min with a material/solvent ratio of 1/20. Under the optimal conditions, the corresponding predicted response value for the total phenolic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The results revealed that acetone, methanol, and ethanol were better solvents for phenolic extraction compared to water only, with the high TP values of 146.26 ± 4.77, 120.78 ± 3.27, and 99.43 ± 1.78mg GAE g -1 , respectively. Polar solvents such as methanol, ethanol, acetone, and water were commonly used to extract polyphenols from plant samples (Yakob et al, 2012;Oreopoulou et al, 2019;Trang et al, 2022) and L. octovalvis (Yakob et al, 2012) in previous studies. Because the extraction process using acetone water obtained the highest polyphenol value, this solvent was determined to be best suitable for extracting polyphenol compounds from L. octovalvis.…”
Section: Extraction Of Polyphenolsmentioning
confidence: 99%
“…The results revealed that acetone, methanol, and ethanol were better solvents for phenolic extraction compared to water only, with the high TP values of 146.26 ± 4.77, 120.78 ± 3.27, and 99.43 ± 1.78mg GAE g -1 , respectively. Polar solvents such as methanol, ethanol, acetone, and water were commonly used to extract polyphenols from plant samples (Yakob et al, 2012;Oreopoulou et al, 2019;Trang et al, 2022) and L. octovalvis (Yakob et al, 2012) in previous studies. Because the extraction process using acetone water obtained the highest polyphenol value, this solvent was determined to be best suitable for extracting polyphenol compounds from L. octovalvis.…”
Section: Extraction Of Polyphenolsmentioning
confidence: 99%